Analisis Pengalaman Belajar Meaningful Learning Melalui Transformasi Matematika Tauhid - Majid, Annis Annafik; Mariana, Neni; Fitri, Ruqoyyah (Jayapangus Press, 2025)
The main competencies of 21st century education emphasize critical thinking and problem-solving skills. A subject with great potential for developing critical thinking and problem-solving skills is mathematics. However, the role of mathematics, which is so important and bridges various sciences, is not in line with its practice. Mathematics is considered difficult, feared and considered an unpleasant lesson because it is not contextually linked. The purpose of this research is to integrate the values of tawhid meaningfully in mathematics learning through the researcher's personal experience so as to produce changes in ways of thinking, ways of understanding and ways of teaching mathematics. This research is transformative research with autoethnography method. This certainly involves the researcher as a subjectivity in obtaining data and utilizing the dimensions of the five ways of knowing owned by transformative research in helping the research process, starting from cultural-self knowing, relational knowing, critical knowing, visionary and ethical knowing and knowing in action. Data collection techniques in obtaining research data include writing critical autoethnography, writing as inquiry and literature study. The results showed that meaningful mathematics learning can be realized through integration with Islamic values, especially tawhid asma wa sifat. This approach not only enriches conceptual understanding, but also touches the spiritual side, so that math no longer feels like a difficult science, hard to understand and separate from life. Through autoethnographic reflection, the researcher found that numbers that were previously considered abstract such as the number 1 and strange odd numbers, turned out to have a deep spiritual depth of meaning when associated with the concept of tawhid.